2018
DOI: 10.3390/en11061330
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Operational Performance of Grid-Connected PV Systems in Selected European Countries

Abstract: This paper presents the results of the analyses of operational performance of small-sized residential PV systems, connected to the grid, in The Netherlands and some other European countries over three consecutive years. Web scraping techniques were employed to collect detailed yield data at high time resolution (5-15 min) from a large number (31,844) of systems with 741 MWp of total capacity, delivering data continuously for at least one year. Annual system yield data was compared from small and medium-sized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…To illustrate seasonal effects, we will show typical summer and winter day data for clear sky, completely overcast, and mixed clear/cloudy conditions. To calculate PV energy yield, we used a single PV module efficiency of 20%, corresponding to using 320 Wp modules of 1.6 m 2 size, and multiplied this with a performance ratio (PR) value of 0.85 to account for temperature and other system losses, which is consistent with well-performing PV systems in the Netherlands [12]. The actual design of a PV system covering façades and roof of a building is facilitated by the availability of 3D drawings of buildings, such as in SketchUp [13].…”
Section: Pv Yieldmentioning
confidence: 99%
“…To illustrate seasonal effects, we will show typical summer and winter day data for clear sky, completely overcast, and mixed clear/cloudy conditions. To calculate PV energy yield, we used a single PV module efficiency of 20%, corresponding to using 320 Wp modules of 1.6 m 2 size, and multiplied this with a performance ratio (PR) value of 0.85 to account for temperature and other system losses, which is consistent with well-performing PV systems in the Netherlands [12]. The actual design of a PV system covering façades and roof of a building is facilitated by the availability of 3D drawings of buildings, such as in SketchUp [13].…”
Section: Pv Yieldmentioning
confidence: 99%
“…The mean value of PR is 78%. As a comparison, values of PR between 48% and 93% have been reported in other works (Munro and Blaesser, 1994;Anis and Nour, 1995;Baltus et al, 1997;Blaesser, 1997;Decker and Jahn, 1997;Erge et al, 2001;Oozeki et al, 2010;Reich et al, 2012;Van Sark et al, 2012, Pelland andAbboud, 2008;Ueda et al, 2009;Eltawil and Zhao, 2010;Hussin et al, 2012;Wittkopf et al, 2012;Díez-Mediavilla et al, 2013;Woyte et al, 2013;Bonsignore et al, 2014;Colantuono et al, 2014;Myong et al, 2015;Tsafarakis and Van Sark, 2015;Kausika et al, 2018;Seme et al, 2019).…”
Section: C) Technical Qualitysupporting
confidence: 57%
“…Over the last decades, numerous monitoring campaigns have allowed to report and analyse the performance of thousands of PV systems worldwide (Anis and Nour, 1995;Baltus et al, 1997;Blaesser, 1997;Decker and Jahn, 1997;Erge et al, 2001;Pelland and Abboud, 2008;Ueda et al, 2009;Eltawil and Zhao, 2010;Hussin et al, 2012;Leloux et al, 2012aLeloux et al, , 2012bWittkopf et al, 2012;Díez-Mediavilla et al, 2013;Woyte et al, 2013;Bonsignore et al, 2014;Colantuono et al, 2014;Leloux et al, 2015;Myong et al, 2015;Taylor et al, 2015a;Tsafarakis and Van Sark, 2015;Kausika et al, 2018;Seme et al, 2019). These studies have shown a wide disparity in performance between the PV systems, with Performance Ratio (PR) values typically comprised between 60% and 90%.…”
Section: Introductionmentioning
confidence: 99%
“…Fault location identification from the measured data is a critical application of data analytics techniques. The GridCloud [78] An open-source platform for real-time data acquisition, sharing, and monitoring FNET/GridEye [75] Visualization of system stress 3D visualization using AVS Express7.3 [79] Visualize real-time power system information and relationship utilizing SCADA data Tableau [80,81] SG data visualization Microsoft Power BI [82] Smart meter data visualization Animation loops [83] Combine periodic snapshots of the grid into time-lapse videos defined across geographic areas Sparklines [83] Summarize trends in time-varying PMU data as word-sized line plots Google Earth [64,84] SG data visualization Cartography and spatial analysis techniques [85] Visualize, yield and performance map of grid-connected PV systems GIS [77] To display real-time operational data…”
Section: Data Miningmentioning
confidence: 99%